The inadequate corpus luteum - W Colin Duncan (Bioscientifica, 2021)
The corpus luteum is the source of progesterone in the luteal phase of the cycle and the initial two-thirds of the first trimester of pregnancy. Normal luteal function is required for fertility and the maintenance of pregnancy. Progesterone administration is increasingly used during fertility treatments and in early pregnancy to mitigate potentially inadequate corpus luteum function. This commentary considers the concept of the inadequate corpus luteum and the role and effects of exogenous progesterone. Progesterone supplementation does have important beneficial effects but we should be wary of therapeutic administration beyond or outside the evidence base.